2009
DOI: 10.1016/j.vetpar.2009.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological characterisation of Echinococcus from food producing animals in India

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 of 27A c c e p t e d M a n u s c r i p t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
4
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 20 publications
9
76
4
3
Order By: Relevance
“…The prevalence in cattle and buffalo was at par where as low prevalence was noticed in pigs and sheep than earlier studies in India (Pednekar et al 2009). Irrespective of the species, the disease was found to be positively correlated with increase in age indicating that no cross immunity occurs with increase in age.…”
Section: Discussioncontrasting
confidence: 44%
“…The prevalence in cattle and buffalo was at par where as low prevalence was noticed in pigs and sheep than earlier studies in India (Pednekar et al 2009). Irrespective of the species, the disease was found to be positively correlated with increase in age indicating that no cross immunity occurs with increase in age.…”
Section: Discussioncontrasting
confidence: 44%
“…These informal groupings were retained for many years but with the advent of molecular characterization they were shown to be genetically distinct (Thompson and McManus, 2001). PCR-based techniques using a variety of genetic loci, and sequencing of nuclear and mitochondrial DNA, coupled with molecular epidemiological studies in endemic areas, confirmed the genetic and morphological distinctness of the host-adapted strains and revealed phylogenetic relationships which support a robust, meaningful taxonomy based on a previously documented nomenclature (Table 2; Bowles et al, 1994;Cruz-Reyes et al, 2007;Harandi et al, 2002;Huttner et al, 2009;Jenkins et al, 2005Lavikainen et al, 2003Moks et al, 2008;Nakao et al, 2013;Pednekar et al, 2009;Romig et al, 2006Romig et al, , 2015Saarma et al, 2009;Thompson et al, 1995Thompson et al, , 2006Thompson, 2001Thompson, , 2008Thompson and McManus, 2002;Tigre et al, 2016). Interestingly, the nomenclature used for these 'species' conforms to that proposed by observational parasitologists in the 1920se60s, before molecular tools were available to confirm and support their morphological descriptions and epidemiological observations Thompson and McManus, 2002;Thompson, 2008).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 63%
“…Furthermore, at the local abattoir level, the lack of legislation for meat inspection and safe offal disposal contribute to the maintenance of domestic cycles of transmission (Irshadullah et al, 1989). Buffaloes and cattle are generally considered the most significant intermediate hosts for sustaining the life cycle (Pednekar et al, 2009). Moreover, a wide range of susceptible captive and wild animals may be involved in transmission which has so far not been studied in detail.…”
Section: Global Distribution Of Alveolar and Cystic Echinococcosismentioning
confidence: 99%